ADOPTION TECHNOLOGY DRIVEN STRATEGIES FOR PERFORMANCE IMPROVEMENT BY MALE AND FEMALE SPORTSPERSONS OF NAGPUR DISTRICT (International Journal of Food and Nutritional Sciences, 2023)
The integration of technology in sports has emerged as a transformative force, offering innovative solutions to enhance athletic performance. This study explores the adoption of technology-driven strategies by male and female sportspersons in Nagpur District, focusing on their utilization patterns, perceived benefits, and challenges. With the increasing availability of advanced tools such as wearable devices, biomechanical analysis systems, virtual reality training, and data analytics, athletes are leveraging these technologies to optimize training, improve performance, and reduce injury risks. However, the extent to which these tools are adopted and their effectiveness across genders remains underexplored. Through a mixed-methods approach, this research investigates the adoption rates, gender-specific preferences, and performance outcomes associated with technology-driven strategies among athletes in Nagpur. Data was collected through surveys, interviews, and performance assessments, targeting a diverse sample of male and female sportspersons across various disciplines. The findings reveal significant differences in technology adoption patterns between genders, with male athletes showing higher engagement in performance analytics, while female athletes emphasized injury prevention and recovery tools. Despite these differences, both groups reported measurable improvements in performance metrics, highlighting the potential of technology to bridge gender disparities in sports. This study underscores the importance of tailored technology-driven strategies to meet the unique needs of male and female athletes. It also provides actionable insights for coaches, sports organizations, and policymakers to promote equitable access to technological resources, fostering a more inclusive and competitive sporting environment in Nagpur District. The research contributes to the growing body of knowledge on the role of technology in sports, emphasizing its potential to drive performance improvement and gender equality in athletics.